Tri pesni o Lenine - Vertov, Dziga (Soviet Union, 1937)
Three short films about Lenin's life and his historical significance. Titles are "In A Black Prison Was My Face"," We Loved Him" and "In the Great City of Stone." Silent film with orchestral score.
Keywords: Fiction films